1993
DOI: 10.1099/0022-1317-74-11-2487
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an in vivo reactivation model of herpes simplex virus from mice trigeminal ganglia

Abstract: Herpes simplex virus type 1 (HSV-1) is transcriptionally active during latent infection in human peripheral sensory ganglia. Viral gene expression includes the latency-associated transcripts (LATs) which have been linked to the ability of the virus to resume replication and reactivate. However, the molecular basis of reactivation and the mechanisms of action of these transcripts are unknown. In order to study these parameters, an in vivo reactivation model is needed. We investigated use of the mouse as the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Similar to the results of this study, it was previously shown that by 3 days p.i., CD8 ϩ T cells begin infiltrating the TG, peaking at 14 days (clear of virus by day 11 p.i. ), declining significantly after clearance of lytic infection, and persisting as latent virus (12,16,(27)(28)(29). In addition, in line with our results, it was previously shown that the level of PD-1 expression during the early stage of human hepatitis C virus (HCV) infection is significantly higher for subjects who progress to chronic HCV infection than for those who clear infection (30).…”
Section: Cd8supporting
confidence: 80%
“…Similar to the results of this study, it was previously shown that by 3 days p.i., CD8 ϩ T cells begin infiltrating the TG, peaking at 14 days (clear of virus by day 11 p.i. ), declining significantly after clearance of lytic infection, and persisting as latent virus (12,16,(27)(28)(29). In addition, in line with our results, it was previously shown that the level of PD-1 expression during the early stage of human hepatitis C virus (HCV) infection is significantly higher for subjects who progress to chronic HCV infection than for those who clear infection (30).…”
Section: Cd8supporting
confidence: 80%
“…However, no evidence to prove a direct role for LATs in reactivation has so far been presented. The other possibility is that this gene(s) functions to promote the ability of HSV-1 to establish latent infection in neurons, increasing the pool of latently infected cells and indirectly improving reactivation ability (3,53). This is supported by the recent observation that HSV-1 reactivation efficacy correlated with its ability to establish latent infection in a high percentage of neurons (66).…”
Section: Discussionmentioning
confidence: 97%
“…This protein may also be involved in apoptosis of neurones that have been infected with HSV (28). The immune system contributes to the establishment of latency by suppressing infection and limiting the spread of the virus at synaptic junctions (29). Latency is accompanied by a chronic inflammatory process at an immunoprivileged site that seems to maintain viral latency and influence viral reactivation without leading to neuronal destruction (30).…”
Section: Pathogenesismentioning
confidence: 99%